Acanthamoeba spp. aggregate and encyst on contact lens material increasing resistance to disinfection - Campolo, Allison; Pifer, Reed; Walters, Rhonda; Thomas, Megan; Miller, Elise; Harris, Valerie; King, Jamie; Rice, Christopher A.; Shannon, Paul; Patterson, Brian; Crary, Monica (Frontiers in Microbiology, 2022)
Acanthamoeba keratitis is often caused when Acanthamoeba contaminate contact lenses and infect the cornea. Acanthamoeba is pervasive in the environment as a motile, foraging trophozoite or biocide-resistant and persistent cyst. As contact lens contamination is a potential first step in infection, we studied Acanthamoeba’s behavior and interactions on different contact lens materials. We hypothesized that contact lenses may induce aggregation, which is a precursor to encystment, and that aggregated encystment would be more difficult to disinfect than motile trophozoites. Six clinically and/or scientifically relevant strains of Acanthamoeba (ATCC 30010, ATCC 30461, ATCC 50370, ATCC 50702, ATCC 50703, and ATCC PRA-115) were investigated on seven different common silicone hydrogel contact lenses, and a no-lens control, for aggregation and encystment for 72 hours. Cell count and size were used to determine aggregation, and fluorescent staining was used to understand encystment. RNA seq was performed to describe the genome of Acanthamoeba which was individually motile or aggregated on different lens materials. Disinfection efficacy using three common multi-purpose solutions was calculated to describe the potential disinfection resistance of trophozoites, individual cysts, or spheroids. Acanthamoeba trophozoites of all strains examined demonstrated significantly more aggregation on specific contact lens materials than others, or the no-lens control. Fluorescent staining demonstrated encystment in as little as four hours on contact lens materials, which is substantially faster than previously reported in natural or laboratory settings. Gene expression profiles corroborated encystment, with significantly differentially expressed pathways involving actin arrangement and membrane complexes. High disinfection resistance of cysts and spheroids with multi-purpose solutions was observed. Aggregation/encystment is a protective mechanism which may enable Acanthamoeba to be more disinfection resistant than individual trophozoites. This study demonstrates that some contact lens materials promote Acanthamoeba aggregation and encystment, and Acanthamoeba spheroids obstruct multi-purpose solutions from disinfecting Acanthamoeba.